Нелінійна динаміка як інструмент прогнозування патологічних змін на електроенцефалограмі - Білошицька, Оксана Костянтинівна (НТУ "ХПІ", 2016)
Розглядаються методи нелінійної динаміки аналізу діяльності електричної активності головного мозку, зокрема, при патологічних змінах. Для аналізу ЕЕГ-сигналів використовувалися метод R/S-аналізу, показник Херста та фазовий портрет. За допомогою методів нелінійної динаміки можна говорити про системні процеси, які відбуваються в головному мозку, та прогнозувати своєчасне виявлення епілептичних нападів.

This article is about the application of nonlinear dynamics to the study of human brain. Paroxysmal electrical discharges periodically cause a variety of brain dysfunctions and the brain activity can be described in frame of dessipative nonlinear chaotic systems. R/S-analysis, Hurst exponent and phase portrait of the system are used to demonstrate multidimensionality of dynamical systems. This work reveals that complicated structure of the brain can be considered as deterministic nonlinear system and can be described with complex mathematical model using parameters mentioned above. The Hurst exponent (the exponent of non-linear dynamic) was counted for three periods of EEG signal (preictal, ictal and postictal). This parameter can be used for qualitative and quantitative estimation of electrical brain activity. Analyzing the phase portraits, it is shown that the complexity of EEG decreases in ictal periods compared with inictal. The results of electrical brain activity investigation will give an opportunity to improve and develope new methods of epileptical treatment, to predict and to prevent epileptical seizures that will lead to improving of life conditions and extending the life span of patients.
Nonlinear dynamics as instruments for prediction of pathological changes in the electroencephalogram
Keywords: ЕЕГ; R/S-аналіз; показник Херста; фазовий портрет; перетворення Фур’є; EEG; R/S-analysis; Hurst exponent; phase portrait